Boiled yam end-user preferences and implications for trait evaluation - Honfozo, L.; Adinsi, L.; Bouniol, A.; Adetonah, S.; Forsythe, L.; Kleih, Uli K.; Hounhouigan, Joseph D.; Fliedel, G.; Akissoe, N.H. (Wiley, 2021)
This study aimed to establish the quality characteristics of raw and boiled yam by involving stakeholders along the food chain using a methodology that includes a state of knowledge review, focus group discussion and individual interviews, participatory processing diagnosis with processors and consumer testing. Predictive characteristics of yam for producing a high‐ and low‐quality boiled yam were related to morphological or physicochemical characteristics: peeled yam discoloration and mucilage content being negatively appreciated while the ease of peeling, viscous state of cooking water and the ease of breaking yam into pieces positively valued. High‐quality boiled yam should be white or yellowish, sticky to the fingers, nonfibrous, easy to chew, crumbly/friable, with a sweet taste and a good smell. The overall liking of boiled yam is greatly penalised by a too dark colour, hard to the touch, no sweet taste and no friability while eating.